2020
DOI: 10.1111/lam.13284
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced microbial safety of channel catfish ( Ictalurus punctatus ) fillet using recently invented medium molecular weight water‐soluble chitosan coating

Abstract: Chitosan with higher molecular weight exhibited higher antimicrobial efficacy against foodborne pathogens. However, the poor water solubility of higher or medium molecular weight chitosan limits its applications. To overcome the challenge, our research team searched for simple preparation procedure for fast‐dissolving medium molecular weight chitosan in water. Throughout the process, we were able to obtain a higher concentration of medium molecular weight water‐soluble (MMWWS) chitosan (400 kDa). The MMWWS chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Usually by mixing different ingredients, the diffraction bands existing in diffractograms sustain some attenuation, diminishing, scattering, and broadening, which are all clear indications of the crystallinity lowering. [32,47,166,174,211,235,239,240] Antibacterial activity is performed by the assessment of the zone of inhibition assay on a solid medium placed in Petri dishes and containing specific media for each microorganism tested [74,125,129,141,171,176,179,187,213,238,[241][242][243][244][245][246][247][248][249][250][251][252][253][254][255][256][257][258][259].…”
Section: X-ray Difractionmentioning
confidence: 99%
“…Usually by mixing different ingredients, the diffraction bands existing in diffractograms sustain some attenuation, diminishing, scattering, and broadening, which are all clear indications of the crystallinity lowering. [32,47,166,174,211,235,239,240] Antibacterial activity is performed by the assessment of the zone of inhibition assay on a solid medium placed in Petri dishes and containing specific media for each microorganism tested [74,125,129,141,171,176,179,187,213,238,[241][242][243][244][245][246][247][248][249][250][251][252][253][254][255][256][257][258][259].…”
Section: X-ray Difractionmentioning
confidence: 99%
“…Several studies reported the use of chitosan as a coating to enhance quality and increase shelf‐life of seafood during frozen and refrigerated storage (Bonilla et al., 2018; Chouljenko et al., 2017; Duan et al., 2010; Li et al., 2020; Mohan et al., 2012; Sathivel et al., 2007). In the above studies, low‐ and medium‐molecular‐weight chitosans were used with acetic acid as a solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is well known as a natural biopolymer with numerous uses in food, agriculture, biotechnology, cosmetics, pharmaceuticals and waste treatment (Kumari & Kishor, 2020). Chitosan prepared from marine sources has the potential for antioxidant and antimicrobial activities in vitro and the ability to be applied in vivo (Younes & Rinaudo, 2015; Kurniasih & Dewi, 2018; Long et al ., 2018; Li et al ., 2020; Karsli et al ., 2021a,b). Chitosan prepared from Litopenaeus vannamei waste exhibited antioxidant efficacy against lipid peroxidation in tuna dark muscle homogenates (Trung & Bao, 2015).…”
Section: Introductionmentioning
confidence: 99%